2011
DOI: 10.4314/ajfand.v11i5.70445
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of <i>ficus carica</i> indigenous to Pakistan

Abstract: The nutritional composition of Ficus carica commonly known as fig is of great interest as it is considered a good source of energy and minerals. Seven samples of fig, cultivated in Pakistan were studied for their physico-chemical properties. All samples had little moisture, less amounts of ash and high volatile matters. Low moisture is favorable in preventing the fermentation of the fruit while high volatiles are responsible for its unique taste. The energy content of the samples ranged between 337.60 -364.70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 14 publications
5
15
1
Order By: Relevance
“…Some species (M. alba, M. nigra, F. racemosa) are preferred due to their foliage yield and delicious fruits, while others (F. carica and M. laviegata) have strong environmental adaptability. These fruits can be eaten fresh or dried and also be processed into juices, paste or pulp [3,4]. A number of detailed studies show the health benefits of these medicinal fruits as they have considerable antimicrobial, antifungal, anti-allergic, antioxidant and antihypoglycemic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Some species (M. alba, M. nigra, F. racemosa) are preferred due to their foliage yield and delicious fruits, while others (F. carica and M. laviegata) have strong environmental adaptability. These fruits can be eaten fresh or dried and also be processed into juices, paste or pulp [3,4]. A number of detailed studies show the health benefits of these medicinal fruits as they have considerable antimicrobial, antifungal, anti-allergic, antioxidant and antihypoglycemic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies were included in this review to evaluate the mineral contents of Ficus carica that is crucial for bone health (Khan et al 2011;Sadia et al 2014;Soni et al 2014). Khan et al (2011) was the earliest to conduct physicochemical profiling of Ficus carica (Sadia et al 2014).…”
Section: Evaluation Of Major Mineral Contents Of Ficus Carica Crucialmentioning
confidence: 99%
“…Three studies were included in this review to evaluate the mineral contents of Ficus carica that is crucial for bone health (Khan et al 2011;Sadia et al 2014;Soni et al 2014). Khan et al (2011) was the earliest to conduct physicochemical profiling of Ficus carica (Sadia et al 2014). Their findings showed that their fig samples contain high amount of potassium (K) at 382.4-611.5 mg/100 g. This is followed by magnesium (Mg) at 110.50-202.40 mg/100 g, Calcium (Ca) 78.72-132.80 mg/100 g and phosphorous (P) at 31.91-76.96 mg/100 g (Khan et al 2011).…”
Section: Evaluation Of Major Mineral Contents Of Ficus Carica Crucialmentioning
confidence: 99%
See 1 more Smart Citation
“…Ficus contains maximum potassium content which is beneficial to hypertension patients and also prevents rapid thinning of bones by stopping the calcium loss in urine. Unique interrelations are present between potassium and copper, potassium and iron and copper and zinc [8]. Its fruit, root and leaves are using in a number of medicine for many disorders like colic, indigestion, diarrhea, sore throats, coughs, bronchial problems, inflammatory, cardiovascular disorders, ulcerative diseases, and cancers.…”
Section: Introductionmentioning
confidence: 99%